2020
DOI: 10.1038/s41598-020-65576-y
|View full text |Cite
|
Sign up to set email alerts
|

Towards non-invasive computational-mechanics and imaging-based diagnostic framework for personalized cardiology for coarctation

Abstract: coarctation of the aorta (coA) is a congenital narrowing of the proximal descending aorta. Although accurate and early diagnosis of COA hinges on blood flow quantification, proper diagnostic methods for COA are still lacking because fluid-dynamics methods that can be used for accurate flow quantification are not well developed yet. Most importantly, coA and the heart interact with each other and because the heart resides in a complex vascular network that imposes boundary conditions on its function, accurate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 70 publications
1
39
0
1
Order By: Relevance
“…Therefore, as an alternative to FVM, LBM is also applied for haemodynamic simulations. [14][15][16] Previous comparison of LBM and FVM in the haemodynamic simulation of a bifurcation in abdominal arteries confirmed that LBM is able to deliver comparable accurate results with less computational cost. Furthermore, the lattice generation process is much easier than FVM grid generation.…”
Section: Introductionmentioning
confidence: 88%
“…Therefore, as an alternative to FVM, LBM is also applied for haemodynamic simulations. [14][15][16] Previous comparison of LBM and FVM in the haemodynamic simulation of a bifurcation in abdominal arteries confirmed that LBM is able to deliver comparable accurate results with less computational cost. Furthermore, the lattice generation process is much easier than FVM grid generation.…”
Section: Introductionmentioning
confidence: 88%
“…In the second step, R SA , C SAC , and C ao were optimized so that maximum and minimum of the aorta pressures were equal to the systolic pressure and diastolic pressure, respectively, measured using a sphygmomanometer in each patient. Because the left ventricle confronts the total systemic resistance and not the specific resistances, and the systemic arteries resistance ( R SA ) is one order of magnitude greater than both the aortic resistance ( R ao ) and systemic vein resistance ( R SV ), we considered R ao and R SV as constants and optimized R SA as the main contributor of the total systemic resistance ( Keshavarz-Motamed et al, 2011 , 2012 , 2014 , 2015 ; Benevento et al, 2015 ; Keshavarz-Motamed, 2020 ; Sadeghi et al, 2020 ). C ao was considered to be 0.6 of C SAC because 60% of the total arterial compliance lives in the proximal aorta ( Stergiopulos et al, 1999 ).…”
Section: Methodsmentioning
confidence: 99%
“…“Cardiology is flow” ( Richter and Edelman, 2006 ) and indeed quantifications of hemodynamics can be immensely valuable for precise diagnosis, however, we still lack precise diagnostic tools for various cardiovascular diseases ( Di Carli et al, 2016 ). There has been an emerging conclusion by many researchers that valvular disease is a complex and mixed disease that also depends on the ventricle and the vascular system states ( Yin, 1987 ; Burkhoff et al, 2005 ; Borlaug and Kass, 2008 ; Taylor and Steinman, 2010 ; Dweck et al, 2012 ; Antonini-Canterin et al, 2013 ; Keshavarz-Motamed et al, 2014 , 2016 ; Ben-Assa et al, 2019 ; Ikonomidis et al, 2019 ; Keshavarz-Motamed et al, 2020 ; Sadeghi et al, 2020 ; Khodaei et al, 2021a , b ). Indeed, the quantitative investigations of hemodynamics in patients with C3VI should take into account the interactive coupling of the valves, ventricle, and the vascular system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Cardiology is flow" [14] and indeed hemodynamic quantification can be immensely valuable for precise and early diagnosis, however, we still lack precise and early diagnostic tools for various cardiovascular diseases because the hemodynamics analysis methods that can be used as engines of such diagnostic tools are not well developed yet [10]. The required quantities for these tools are local and global hemodynamics metrics [15][16][17][18][19][20][21][22][23][24][25][26][27][28]: (1) Metrics of circulatory function (local), e.g., detailed information of the dynamics of the circulatory system, and (2) Metrics of cardiac function (global), e.g., heart workload and its contribution breakdown of each component of the cardiovascular diseases. Assessments of hemodynamics, if available, would provide valuable information about the patient's state of cardiac deterioration as well as heart recovery and could be used for planning complex valvular-vascular-ventricular disease (C3VD) interventions and making critical clinical decisions with life-threatening risks.…”
Section: Introductionmentioning
confidence: 99%